Coordination modulation of hydrated zinc ions to enhance redox reversibility of zinc batteries - Chen, Song; Ji, Deluo; Chen, Qianwu; Ma, Jizhen; Hou, Shaoqi; Zhang, Jintao (Nature communications, 2023)
The dendrite growth of zinc and the side reactions including hydrogen evolution often degrade performances of zinc-based batteries. These issues are closely related to the desolvation process of hydrated zinc ions. Here we show that the efficient regulation on the solvation structure and chemical properties of hydrated zinc ions can be achieved by adjusting the coordination micro-environment with zinc phenolsulfonate and tetrabutylammonium 4-toluenesulfonate as a family of electrolytes. The theoretical understanding and in-situ spectroscopy analysis revealed that the favorable coordination of conjugated anions involved in hydrogn bond network minimizes the activate water molecules of hydrated zinc ion, thus improving the zinc/electrolyte interface stability to suppress the dendrite growth and side reactions. With the reversibly cycling of zinc electrode over 2000 h with a low overpotential of 17.7 mV, the full battery with polyaniline cathode demonstrated the impressive cycling stability for 10000 cycles. This work provides inspiring fundamental principles to design advanced electrolytes under the dual contributions of solvation modulation and interface regulation for high-performing zinc-based batteries and others. Zinc-based batteries suffer from the dendrite growth and surface passivation of zinc derived from the unfavourable deposition and side reactions. Here, the authors modulate the coordination chemistry of hydrated zinc ions via electrolyte-design and gain insights into the reversible cycling of long-lived zinc electrode.